2020
DOI: 10.20535/2410-8286.214539
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Language and Cross-Cultural Competence Through Telecollaboration

Abstract: This paper presents an experiment which focused on determining if a telecollaborative project work would help enhance students' foreign language skills and cross-cultural competence. Students from Igor Sikorsky Kyiv Polytechnic Institute and the Polytechnic University of Valencia worked together during the fall term in 2020, in which 56 Ukrainian and Spanish students were engaged in a telecollaborative programme -32 were master degree students at Igor Sikorsky Kyiv Polytechnic Institute, whereas the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Los resultados del progreso en la mejora en habilidades comunicativas en inglés y competencias digitales se han presentado en diferentes publicaciones (Candel-Mora et al, 2020;Casañ-Pitarch et al, 2020;, no obstante para este trabajo preliminar destacamos los resultados del progreso de los participantes en la adquisición de la competencia intercultural, clave para la enseñanza de inglés global.…”
Section: Resultsunclassified
“…Los resultados del progreso en la mejora en habilidades comunicativas en inglés y competencias digitales se han presentado en diferentes publicaciones (Candel-Mora et al, 2020;Casañ-Pitarch et al, 2020;, no obstante para este trabajo preliminar destacamos los resultados del progreso de los participantes en la adquisición de la competencia intercultural, clave para la enseñanza de inglés global.…”
Section: Resultsunclassified
“…Fourteen papers also demonstrated how students prepared for intercultural teamwork to ensure that every team member could work together effectively and break down barriers. Most of them (n = 11) reported that students attended cultural orientation courses such as courses on cross-cultural behaviors or teambuilding, technical courses for virtual teams, and language training courses held by the relevant institutions or programs [41,54,61]. In addition, a few of these 14 articles (n = 5) mentioned predeparture meetings before short-term study abroad, and informal social activities intended to develop a sense of group identity [38,48,62].…”
Section: Level Of Collaboration and Teamwork Preparationmentioning
confidence: 99%
“…The lack of scientifically grounded classification of integral learning outcomes in higher education has caused terminological discordance. In some publications, along with established conceptual categories of "key competencies", "professional competence", "communicative competence", "foreign language communicative competence" (Bogush et al, 2019;Kachmarchyk et al, 2019;Мammadov et al, 2019) etc., arguable terms are adopted, which significantly complicate modern scientific discourse: "cross-curricular competencies" (Gewerc et al, 2011), "technical competency" (Bovermann et al, 2018;Sinchev et al, 2018), "intercultural competence" (Tomozeiu et al, 2016;Holubnycha et al, 2019;Casañ-Pitarch et al, 2020), "traditional teaching competencies", "original teacher competency", "traditional competencies", "individual competencies", "core competencies", "specific competencies", "most critical competencies" (Weng et al, 2020); "cultural competence", "intercultural communicative competence" (Padua and Gonzalez Smith, 2020).…”
Section: Theoretical Overviewmentioning
confidence: 99%